Education as Cultivation in Chinese Culture
VIII, 288 p. 20 illus.
Keywords: Given the increasing global interest in Chinese culture, this book uses case studies to describe and interpret Chinese cultivation in contemporary Taiwanese schools. Cultivation is a concept unique to Chinese culture and is characterized by different attitudes towards teaching and learning compared to Western models of education. The book starts with a discussion of human nature in Chinese schools of philosophy and levels of goodness. Following the philosophical background is a presentation of how cultivation is practiced in Chinese culture from prenatal through high school education. The case studies focus both on how students are cultivated as they become members of Chinese society, and on what role teachers play in cultivating the children in school. In addition, common practices of Chinese educational institutions, including public schools, families, and organizations such as private cram schools, are introduced and explained. In closing, the book presents a critique of the modern school reform movement and the conflicts between the reform proposals and traditional practices. Based on the collective work of Taiwanese researchers in the fields of education, history and anthropology, the book identifies the purpose of education as cultivating virtue, the process of creating an ideal person who serves society, and describes the way teachers have carried on this tradition despite its faltering status in contemporary educational discourse and in the face of reform movements.